Better Alone Than in Bad Company: New Species of Caudofoveate Limifossorid (Mollusca, Aplacophora) Unravels Patterns of Distribution Hidden in the Deep Atlantic - Passos, Flávio Dias; Corrêa, Paulo Vinicius Ferraz; Miranda, Marcel Sabino (Frontiers in Marine Science, 2021)
Aplacophorans are common inhabitants of the deep-sea, where many places remain unexplored regarding their biodiversity. Filling a gap in knowledge about these animals from the South Atlantic, Scutopus variabilis sp. nov. (Caudofoveata, Limifossoridae) is described; further, species distribution modelling (SDM) was performed to elucidate the distribution patterns of Atlantic species of Scutopus. The type materials of S. megaradulatus Salvini-Plawen, 1972 and S. chilensis Salvini-Plawen, 1972, were examined and a search was performed for specimens of Scutopus held in museum collections. Scutopus variabilis sp. nov. has a slender and highly variable body form and a very distinct suture line is present midventrally. Two dominant types of trunk sclerites were observed by Scanning Electron Microscopy (SEM): one elongated with lateral margins slightly concave in medial portion, and another longer, with narrower base; its radula bears up to eight rows of heavily sclerotized teeth bearing 12-16 small denticles. The species occurs in a wide bathymetric range (40-1300 m), being more abundant at the edge between the continental shelf and upper slope. Outside the areas from where these samples were obtained, suitable areas for S. variabilis sp. nov. were found in the Southern Caribbean Sea (from where S. megaradulatus is recorded) and in the Brazilian Northern coast; the Gulf of Mexico and the Brazilian Northeastern coasts were found as unsuitable. Species of Scutopus appear to exhibit different patterns of geographical distribution: the European S. ventrolineatus Salvini-Plawen, 1968 and S. robustus Salvini-Plawen, 1970 are known as widely distributed, while non-European representants, the American S. megaradulatus, S. chilensis and S. variabilis sp. nov., and the Japanese S. schanderi Saito and Salvini-Plawen, 2014 and S. hamatamii Saito and Salvini-Plawen, 2014 have more restricted distributions. However, clear and definite patterns of distribution of some of these species are probably blurred by sampling bias, for the European area is better studied. In the Atlantic, the SPM showed that species of Scutopus occur in a way that overlapping is minimized. Great sampling efforts combined with detailed descriptions based on SEM have revealed an interesting, abundant and up to now undescribed Brazilian deep-sea malacofauna.